The impact of carbon disclosure on firm value: Examining the role of institutional ownership in the energy sector - Rachmadhika, Hendra Arie; Firmansyah, Amrie (Universitas Padjadjaran, 2025)
This study examines the influence of carbon disclosure on firm value with institutional ownership as a moderator in energy sector companies listed on the Indonesia Stock Exchange during 2019-2022. Carbon disclosure is measured using the disclosure scale developed by Bae Choi et al. (2013a), the percentage of institutional ownership in the company to calculate institutional ownership, and Tobin's Q to calculate firm value. This study uses data from energy sector companies listed on the Indonesia Stock Exchange for the observation period of 2019-2022, with a total of 80 observations through purposive sampling. The results show that carbon disclosure has a negative effect on firm value. However, institutional ownership weakens the negative influence of carbon disclosure on firm value. The results of this study can provide insights into the factors that can increase firm value for investors. This study is expected to provide a perspective for investors to make investment decisions in the capital market by looking at information related to carbon disclosure conducted by companies.